(3Yf CHh eSde Hf YQHis - (3CHh eSde GdCUagGfj , eMeO Hf HMQ GdCUagGfj, CHh eSde,J (B322 (3g` s
(3ChdgG (B:s
(3bGd ehdGfG GdCYXe CHj eSde hHYV CNhGdg hef cJH GdOYhI GdgGTejI hGdOhdI GdYHGSjI hcGf eedhc dYjSi Hf eYbd s
(3BNQgG (B:s
(3hbJd CHG eSde hGeJOJ GdOhdi GdYHGSjI GeJOGOkG WhjdkG MJi Cf HdZ YOO NdaGFge fjakG hKdGKjf hcGf eOI NdGaJge NeS eGFI hCQHYI hYTQjf hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdcJGH YHGQI Yf MGTjI Ydi cJGH HGddZI GdaGQSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B50 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B97s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdJGQjNs